The rise of Chinese funds to infrastructure : trade and investment in Tanzania - Mumwi, Caroline Simon (My University, 2018)
The rise of China has given attention to most literatures in the international relations by well thought-out to be the most discussed topic. It can be seen that China– Tanzania relationship is considered as a “special” due to their history that can be traced way back during colonial and post-colonial era. But today the relationship is considered to be far better than the one in the 1970s due to globalization influence and China’s diplomatic relations such as using no string attached policy, Foreign Aid and Investment, Economic interdependency (Trade and diplomatic relations) and use of soft power which has been a source of attraction to many African countries including Tanzania. This research report attempts to understand Chinese engagement in Tanzania and its impact towards the population. This research used a semi-structured questionnaire inform of interview. The interview was more focused on different perceptions from Tazara railway managers in regard to China–Tanzania relations and the development of the railway. The research report further used both qualitative and quantitative analysis, and the findings indicate positive (opportunities) and negative (challenges) for ChinaTanzania relations. The research finding shows that China has generated great positive impact to Tanzania especially in economic development such as Trade, Investments and Infrastructure as well as political development involving good diplomatic relationship, and cultural exchange between the two countries. Nevertheless, still there are some challenges faced between China-Tanzania relationship such as, corruption, outdated railway system, poor working conditions for the railway workers, just to mention a few. Lastly, this research indicates recommendations on how to improve on the “special” relationship between the two countries such as, creating more strong policies which will protect Tanzania’s interest and make sure the relationship is both mutual and beneficial to both parties, but we should also consider creating more institutions to enhance genuine relationship.
A research report submitted in partial fulfillment of the requirements for the degree of Master in International Relations, University of the Witwatersrand, 2018
Keywords: Investments, Chinese--Africa; China--Foreign relations--Africa